Coupling of Advanced Oxidation Technologies and Biochar for the Removal of Dyes in Water (2022)
ABSTRACT: When dyes are discharged in water bodies, mutagenic, carcinogenic and teratogenic effects may be caused in both aquatic organisms and human beings. The use of biochar and the implementation of advanced oxidation processes (AOPs) are alternative treatments that have been used individually in the removal of dyes in wastewater. Besides being effective processes acting separately, biochar and AOPs can be coupled, exhibiting synergetic effects in the treatment of dyes contained in water. This work deals with the methods implemented to produce biochar from biomass, its mechanism in the removal of dyes and associated sustainability issues. Additionally, the main AOPs that have been utilized for the removal of dyes from water are covered, as well as the biochar- AOP combined processes. The future prospects for the removal of dyes from water have been also addressed. The coupling of biochar to AOPs has been proven to be more effective in the removal and mineralization of dyes than the individual treatments. In this regard and considering the scarce studies in the field, new horizons are opened on the treatment of water polluted with dyes.